2013
DOI: 10.2298/avb1306549j
|View full text |Cite
|
Sign up to set email alerts
|

Influence of physical activity of racehorses on lactate dehydrogenase and creatine kinase activities, and protein synthesis

Abstract: The aim of the research was to assess the effects of physical activity of various intensity on the degree of damage to certain organs resulting from increased free radical production, as well as the adaptability of the organism to physical exercise.Two groups of healthy 3-5-year-old full-blooded racehorses were assessed. The first one ran a 2400-meter gallop race, which is considered a short-lasting, intense physical activity; lipid status was assessed prior to, and 48 and 72 h after the race. The second group… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 25 publications
0
9
0
1
Order By: Relevance
“…The appearance of a cellular enzyme such as LDH in the extracellular space is a useful marker of disrupted cellular integrity. There are five forms of LDH (isoenzymes LDH 1 -LDH 5 ) and the distribution of each isoenzyme varies between tissues (Jović et al, 2013). We observed that only LDH 5 , related to liver damage, was significantly increased in Theileria infected horses.…”
Section: Discussionmentioning
confidence: 67%
“…The appearance of a cellular enzyme such as LDH in the extracellular space is a useful marker of disrupted cellular integrity. There are five forms of LDH (isoenzymes LDH 1 -LDH 5 ) and the distribution of each isoenzyme varies between tissues (Jović et al, 2013). We observed that only LDH 5 , related to liver damage, was significantly increased in Theileria infected horses.…”
Section: Discussionmentioning
confidence: 67%
“…The increased activity of LDH found in plasma of workers in this study were probably an outcome of cellular membrane destruction due to increased peroxidation .The distribution of LDH isoenzymes can indicate the potential damage to certain organs (Jović et al 2013), according to their tissue specificity. The revealed LDH 1-5 isoenzyme distribution showed variations in results among two groups, depending on the degree of oxidative damage in each tissue.…”
Section: Discussionmentioning
confidence: 52%
“…Varios autores han descrito el aumento de la CK pos-ejercicio ejercicio por el aumento de la permeabilidad del sarcolema (Piccione et al 2009;Jović et al 2013;Mami et al 2019). Según Piccione et al (2009), los niveles de CK se relacionan con el estado de entrenamiento.…”
Section: Discussionunclassified